MR Imaging of Autopsy-Proved Paraneoplastic Limbic Encephalitis in Non-Hodgkin Lymphoma - Thuerl, Christina; Müller, Klaus; Laubenberger, Jörg; Volk, Benedikt; Langer, Mathias (American Journal of Neuroradiology, 2003)
Summary: We report the case of a 26-year-old man with precursor T-cell acute lymphoblastic leukemia who developed paraneoplastic limbic encephalitis that was diagnosed on the basis of MR imaging findings and was proved post mortem. In our MR imaging studies, fluid-attenuated inversion recovery images and diffusion-weighted echo-planar images clearly depicted bilateral involvement of the medial temporal lobes and multifocal involvement of the brain, whereas T2-weighted turbo spin-echo images failed to show the changes.